PENGARUH DUKUNGAN SUPERVISOR DAN IKLIM ORGANISASIONAL TERHADAP SERVICE-ORIENTED ORGANIZATIONAL CITIZENSHIP BEHAVIOUR PADA KARYAWAN HOTEL DI KOTA PADANG - Rio Aprianto; Thamrin Thamrin; Syahrizal Syahrizal (Universitas Negeri Padang, 2019)
The purpose of this study was to determine the effect of the influence of Supervisor Support and Organizational Climate on Service-Oriented Organizational Citizenship Behavior in Hotel Employees in the City of Padang. This type of research is descriptive causative. This research was conducted in the city of Padang. While the time of the study was conducted in 2018. The population in this study were 4-star hotel employees in Padang city with a sample of 100 people taken by simple random sampling. Data is processed using multiple linear regression using SPSS 16.0. The results showed that supervisor support had a significant positive effect on Service-Oriented Organizational Citizenship Behavior, organizational climate had a significantly positive effect on Service-Oriented Organizational Citizenship Behavior at α = 0.05Keyword: Supervisor Support, Organizational Climate, OCB, SO-OCB